Perceptions on the relationship between culture and developement : a case study of iban community in Nanga Mejong, Skrang, Sarawak, Malaysia - Isobeth, Bana (Universiti Malaysia Sarawak (UNIMAS), 2005)
The Iban have changed because they desired an improvement in their living, economic status and not to be left out in the modernizing society in Sarawak. In the process, the iban have to sacrifice many aspects of their traditional living values. This study is about the perception of the iban community in Nanga Mejong, Skrang on the topic of the relationship between culture and development. It was done using qualitative research methods. The methods include in-depth interview with the tuai rumah, focus group interviews and fielwork participations. The focus groups interviews consist of three different groups; the men's group (the longhouse's committee), the women's group and the youth's group.